Digestion and absorption of red grape and wine anthocyanins through the gastrointestinal tract. (January 2019) - Han, Fuliang; Yang, Ping; Wang, Hua; Fernandes, Iva; Mateus, Nuno; Liu, Yangjie
Abstract: Background: Anthocyanins are a major class of phenolic compounds present in red grapes and red wine. They have been reported to possess multiple health-promoting properties. However, the bioavailability of anthocyanins has been reported to be extremely low. In order to better associate anthocyanin consumption to any health-promoting properties, it is very important to understand how grape and wine anthocyanins are digested and metabolized through the gastrointestinal tract and how anthocyanins and their metabolites are absorbed. Scope and approach: This review focuses on the digestion and absorption of grapes and wine anthocyanins through the gastrointestinal tract, including oral cavity, stomach and intestinal tract. Moreover, we discussed the major factors that could affect the digestion and metabolism of anthocyanins. Key findings and conclusions: In the oral cavity, the pH condition and enzymes secreted from bacteria may lead to the hydrolysis of anthocyanins to phenolic acids or the corresponding aglycones. However, anthocyanins are relatively stable and can be absorbed in the stomach with only a small portion being hydrolyzed. The intestine is the main site for the metabolism and absorption of anthocyanins where microbiota and alkaline condition could catabolize anthocyanins into small molecular phenolic acids and aldehydes. Both anthocyanins and their degraded products can be transported through the intestinal epithelium via passive diffusion or active transporters. Active transporters include hexose transporter, ATP-binding cassette transporters and monocarboxylic acid transporters. In conclusion, the anthocyanins can exert their health benefits not only via their intact compounds but also via degraded products/metabolites. However, further studies are still required to explore in detail the mechanism of digestion and absorption of anthocyanins in red grapes and wine. Highlights: Anthocyanins can be absorbed in the stomach with only a small portion being hydrolyzed. Intestinal microbiota and pH play important roles in catabolizing anthocyanins. The degradation products of anthocyanins include phenolic acids, phenol aldehydes and phenols. The anthocyanins absorption is related to SGLT1, GLUT2, BCRP, MRP, P-gp and MCT transporters.